Modelling and simulation of the control of cylindrical friction-driven load system - Ji, Wei Gang (2008)
This dissertation address the problem from the control view, by proposing a control stratgy that enables the control of the load cylinder orientation, the reduction of vibration and the rejection of disturbancesm whilst at the same time minimizing the settling time.